Prospekty, drobne katalogi, cenniki i ogłoszenia księgarskie. 1899-1901" - A., Fromm; N., Kamieński; Jarosław, Leitgeber; Karol, Miarka; [?], Mittler; [?], Schmidt; J., Zaleski St.; Wilhelm, Zukerkandel; M., Arct; W., Babicki; Michał, Bazewicz Józef; [?], Benziger; et al. (1897)
Arct M., Warszawa 1900-1901, (6), nr 163-165, 169-170, 199. - "Ateneum", Warszawa 1900, nr 114. - Bazewicz J. M., Warszawa 1900, nr 72. - Benziger & Co., Einsiedeln 1900, nr 99. - "Biblioteka Dzieł Chrześcijańskich", Warszawa 1900-1901, (2), nr 89, 179. - "Biblioteka Dzieł Wyborowych", Warszawa 1899-1901, (6), nr 27, 46, 53, 108, 134, 198. - "Biblioteka Warszawska", Warszawa 1899-1901, (6), nr 48, 88, 110, 181, 202, 205. - "Bocian", Poznań 1901, nr 149. -
1000,00
Keywords: Bydgoszcz; księgarnia - Mittler; Kraków; księgarnia - Kavka Stefan; czasopismo - "Nowe Słowo"; Litografia Akademicka - Salba M; Spółka Wydawnicza Polska; Berlin; księgarnia - Parey Paul; Bytom; wydawnictwo - "Katolik"; Cieszyn; księgarnia - Feitzinger Edward; Einsiedeln; księgarnia - Benziger & Co; Freinwalde n. Odrą; czasopismo - "Dla Wszystkich"; Grudziądz; czasopismo - "Gospodarz"; Hamburg; księgarnia - Grand Henri; czasopismo - "Ilustracja Polska"; czasopismo - "Pogląd na Świat"; czasopismo - "Gazeta Szkolna"; księgarnia - Gebethner G. i Sp; Lipsk; księgarnia - Schmidt & Günther; księgarnia - Brockhaus F. A; Bibliographisches Auskunftsbureau - Gracklauer O; księgarnia - Friedrich Wilhelm; Łódź; księgarnia - Fiszer (Fischer) Ludwik; Lwów; Towarzystwo Wydawnicze; Wydawnictwo "Studiów nad Historią Prawa Polskiego"; Drukarnia Ludowa; Mikołów; Księgarnia, Wydawnictwo Dzieł Ludowych - Miarka Karol; Poznań; Centralne Towarzystwo Gospodarcze w Wielkim Księstwie Poznańskim; księgarnia - Leitgeber Jarosław i Sp; Księgarnia Katolicka; księgarnia - Kamieński N. i Sp; czasopismo - "Kurier Poznański"; czasopismo - "Praca"; czasopismo - "Sprawy Okowiciane"; Drukarnia i Księgarnia św. Wojciecha; księgarnia - Cybulski A; drukarnia - Chocieszyński Fr; czasopismo - "Bocian znad Gopła, Wisły, Warty i Odry"; czasopismo - "Górnoślązak"; czasopismo - "Przegląd Kościelny"; Księgarnia Polska Wiktora Tempłowicza; Stuttgart; Deutsche Verlags-Anstalt; Toruń; drukarnia - Buszczyński S; Warszawa; czasopismo - "Zdrowie"; czasopismo - "Książka"; Księgarnia Polska J. Sikorskiej; czasopismo - "Kurier Polski"; drukarnia - Laskauer P. i W. Babicki; czasopismo - "Meloman"; Muzeum Przemysłu i Rolnictwa; księgarnia, drukarnia - Orgelbranda S. Synowie; księgarnia - Paprocki Teodor i Ska; czasopismo - "Przegląd Filozoficzny"; czasopismo - "Słowo"; czasopismo - "Strumień"; czasopismo - "Świat"; czasopismo - "Świat Artystyczny"; czasopismo - "Światło"; księgarnia - Trepte Konstanty; księgarnia - Wende E. i Ska; czasopismo - "Wędrowiec"; czasopismo - "Wieczory Rodzinne"; czasopismo - "Wiek"; czasopismo - "Wielka encyklopedia powszechna ilustrowana"; czasopismo - "Wisła"; Warszawskie Towarzystwo Opieki nad Zwierzętami. Komitet Damski; księgarnia - Zaleski St. J; czasopismo - "Ziarno"; Kasa im. Józefa Mianowskiego - Fundacja Popierania Nauki; czasopismo - "Głos"; księgarnia - Gebethner i Wolff; czasopismo - "Gazeta Polska"; księgarnia - Fiszer Jan; czasopismo - "Farmaceuta Polski"; czasopismo - "Encyklopedia Wychowawcza"; czasopismo - "Ekonomista"; czasopismo - "Chimera"; czasopismo - "Chemik Polski"; księgarnia - Bolcewicz Bronisław; czasopismo - "Biblioteka Warszawska"; czasopismo - "Biblioteka Dzieł Wyborowych"; czasopismo - "Biblioteka Dzieł Chrześcijańskich"; wydawnictwo - Bazewicz Józef Michał; czasopismo - "Ateneum"; księgarnia - Arct M